2014
DOI: 10.1242/dev.101931
|View full text |Cite
|
Sign up to set email alerts
|

The actin-binding protein profilin is required for germline stem cell maintenance and germ cell enclosure by somatic cyst cells

Abstract: Specialized microenvironments, or niches, provide signaling cues that regulate stem cell behavior. In the Drosophila testis, the JAK-STAT signaling pathway regulates germline stem cell (GSC) attachment to the apical hub and somatic cyst stem cell (CySC) identity. Here, we demonstrate that chickadee, the Drosophila gene that encodes profilin, is required cell autonomously to maintain GSCs, possibly facilitating localization or maintenance of E-cadherin to the GSC-hub cell interface. Germline specific overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 40 publications
8
45
1
Order By: Relevance
“…2D). Our results differ somewhat from those in a recent analysis of Chic by Shields et al (2014), who found that Chic knockdown resulted in fewer Tj-positive cells. This difference is likely to be due to our use of a different UAS driver and RNAi line to obtain a weaker knockdown of Chic.…”
Section: Chic Is Required In the Soma For Fertilitycontrasting
confidence: 99%
See 1 more Smart Citation
“…2D). Our results differ somewhat from those in a recent analysis of Chic by Shields et al (2014), who found that Chic knockdown resulted in fewer Tj-positive cells. This difference is likely to be due to our use of a different UAS driver and RNAi line to obtain a weaker knockdown of Chic.…”
Section: Chic Is Required In the Soma For Fertilitycontrasting
confidence: 99%
“…2L,M). In a recent study, Shields et al (2014) obtained results consistent with those that we describe here, supporting our findings that somatic Chic knockdown leads to defects in somatic differentiation and germline proliferation.…”
Section: Chic Is Required In the Soma For Fertilitysupporting
confidence: 92%
“…Physical association between ECs and germ cells is crucial for GSC differentiation (Jin et al, 2013;Kirilly et al, 2011;Schulz et al, 2002;Shields et al, 2014). Thus, loss of extensive physical contact with ECs per se could account for the downregulation phenotypes of stat, woc and zfh1.…”
Section: Soma-germline Association and Germ Cell Differentiationmentioning
confidence: 99%
“…dom is essential for stem cell maintenance in the testis (Morillo Prado et al, 2013). chic, the Drosophila gene that encodes profilin, is required to maintain GSCs in a cell-autonomous manner, possibly by regulating the GSC-hub cell interface (Shields et al, 2014). In our screen, knockdown of dom or chic (Fig.…”
Section: Gsc Self-renewal Screen In Fly Testesmentioning
confidence: 99%
“…In addition to the key molecules in the signaling pathways mentioned above, many other factors also regulate the self-renewal and differentiation of stem cells in the testis. Epigenetic factors, microRNAs, actin-binding proteins, nuclear lamins and RNA-binding proteins have all been shown to affect the activity of stem cells in the testis (Chen et al, 2014Cherry and Matunis, 2010;Eun et al, 2013;Pek et al, 2009;Shields et al, 2014). Traditional studies of genes that regulate stem cell activity in testes have relied on mosaic analysis or genetic screens for male sterility in homozygous mutant animals.…”
Section: Introductionmentioning
confidence: 99%